Factors determine Islamic banking performance in Malaysia: a multiple regression approach - Abduh, Muhamad; Alias, Aizat (International Association of Islamic Banks, 2014)
Evidence has shown that Islamic banking is experiencing tremendous development since the last three decades, especially in Malaysia. This study is aimed at investigating factors that determine the Islamic banking performance in Malaysia, particularly in the period of 2006 to 2010. The predictors are loan loss provision to total assets, net loans to total assets, total overhead cost to total assets, shareholders equity ratio, and bank size which represent internal factors and GDP and inflation which represent external factors. Pooled OLS method shows that loan loss provision to total assets, total overhead cost to total assets, and inflation are the significant variables affecting the performance of Malaysia Islamic banking in the period analyzed.